Mentholated cigarettes and smoking-related cancers revisited: An ecologic examination - Kabat, Geoffrey C. (2012)
The US Food and Drug Administration is assessing whether menthol should be banned as an additive to cigarettes. An important part of this determination concerns the health effects of mentholated relative to non-mentholated cigarettes. We examined the ecologic association between sales of mentholated cigarettes for the period 1950–2007, menthol preference by race and sex, and incidence rates of four tobacco-related cancers during 1973–2007. Total sales of mentholated cigarettes (market share) increased from about 3% in 1950 to slightly less than 30% in 1980 and remained fairly stable thereafter. Additional data show consistently that, compared to White smokers, Black smokers favor mentholated cigarettes by roughly a 3-fold margin. Differences in the incidence of lung cancer, squamous cell cancer of the esophagus, oropharyngeal cancer, and laryngeal cancer by race and sex and trends over a 35-year period, during which menthol sales were relatively stable and during which Black smokers were much more likely to smoke mentholated cigarettes compared to Whites, are not consistent with a large contribution of menthol, over and above the effect of smoking per se.